Binary Neutron Star Mergers After GW170817 - Ciolfi, Riccardo (Frontiers in Astronomy and Space Sciences, 2020)
The first combined detection of gravitational waves and electromagnetic signals from a binary neutron star (BNS) merger in August 2017 (an event named GW170817) represents a major landmark in the ongoing investigation of these extraordinary systems. In this short review, we discuss BNS mergers as events of utmost importance for astrophysics and fundamental physics and survey the main discoveries enabled by this first multimessenger observation, including compelling evidence that such mergers produce a copious amount of heavy r-process elements and can power short gamma-ray bursts. We further discuss some remaining key open questions regarding this event and BNS mergers in general, focusing on the current status and limitations of theoretical models and numerical simulations.